Biomass-Derived Carbon Dots and Their Sensing Applications - Jiang Fan; Lei Kang; Xu Cheng; Di Liu; Sufeng Zhang (Nanomaterials, 2022)
Carbon dots (CDs) can be widely used in the field of sensing because of its good water solubility, low toxicity, high fluorescence stability and excellent biocompatibility. It has become a popular trend to prepare high-value, inexpensive, renewable and environmentally friendly CDs sensors from biomass resources. This article reviewed the research progress of biomass-derived CDs as chemical, physical and biological sensors in recent years and studied their preparation processes and sensing abilities. Furthermore, the prospects and challenges of biomass-CDs sensors were discussed. This article is expected to provide inspirations for the design, preparation and application of biomass-CDs sensors in the future.